Penerapan Model Kooperatif Tipe STAD Untuk Meningkatkan Kemampuan Peserta Didik Dalam Berkreasi Tari Sederhana - I Ketut Muada; I Putu Rispa Aditya Mardana; I Gusti Ayu Putu Astini (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to evaluate the impact of implementing the STAD Cooperative Model on the learning outcomes of 10th-grade Fashion students in the Cultural Arts subject for the academic year 2023/2024. The formulation of the problem is whether this model can enhance students' academic achievements. The research objectives include evaluating the learning outcomes of students through the application of this model and providing a comparative study for students planning further research. The theoretical benefits of this research lie in its contribution as a foundation for subsequent studies, enabling other researchers to enhance problem-solving abilities for students. Practically, this study is expected to make a positive contribution to schools, teachers, and students. For schools, it is anticipated to improve the quality of education, especially in teaching cultural arts to enhance the academic achievements of students. For teachers, this research can serve as a reference in developing cultural arts education and other learning processes. Additionally, this study provides insights for 10th-grade Fashion students at SMK Negeri 3 Denpasar to improve their learning outcomes in cultural arts. Through the evaluation of the impact of implementing the STAD Cooperative Model, this research can serve as a foundation for developing more effective teaching strategies, contributing to the enhancement of education quality at the vocational high school level.